(untitled) (Journal of Engineering, 2013)
This paper presents a numerical simulation for the combined effect of surface roughness and non-Newtonian behavior of the lubricant on the performance of misaligned journal bearing. The modified Reynolds equation to include the effect of non-Newtonian lubricant and bearing surface roughness has been formulated. The model accounts for the lubricant viscosity dependence on temperature and shear rate. In order to make a complete thermo-hydrodynamic analysis (THD) of rough surface misaligned journal bearing lubricated with non-Newtonian lubricant, the modified Reynolds equation coupled with the energy, heat conduction equations, the equation related the viscosity and temperature with appropriate boundary conditions have been solved simultaneously. The performance characteristics of the bearing were presented with different roughness parameter for the pressure, temperature, load carrying capacity, misalignment moment and friction force. The computer program prepared to solve the governing equations of the problem has been verified by comparing the results obtained through this work with that published by different workers. It has been found that the results are in a good agreement .The results obtained in the present work showed that the surface roughness characteristics of opposing surfaces and its orientation play an important role in affecting the performance parameters of the bearing. It has been shown that the load in rough aligned journal bearing is higher than that in rough misaligned journal bearing for all surface roughness patterns (γ). An increase in load has been calculated and found to be 29.5% for the bearing with moving roughness while it becomes 32% for the bearing with stationary roughness.